Hepatitis B virus genotype and mutants and the risk of hepatocellular carcinoma - Camillo Porta (Frontiers Media S.A., 2011)
In the August issue of the authoritative Journal of the National Cancer Institute, a research group from Taiwan reported the results of a huge study aimed at assessing a possible association between Hepatitis B virus (HBV) genotypes and common variants in the precore and basal core promoter (BP) regions and the risk of hepatocellular carcinoma (HCC)...